LA FORMAZIONE Dl GORNO NEI DINTORNI Dl DOSSENA E Dl GORNO (PREALPI BERGAMASCHE) ANALISI Dl UNA LAGUNA TRIASSICA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
A Triassic lagoon has been identified in the Bergamasc Alps, northern Italy. It is bordered, to the south, by a volcanic mainland, with fluviatile and deltaic depositional systems, and northwards by a peritidal carbonate platform. The Triassic lagoon is characterized by mixed terrigenous and  carbonate sedimentation. Four main zones have been distinguished:Zone 1a is situated near the mouthes of the rivers and corresponds to the subaqueous part. of the  delta. Feldspatic litharenites and siltstones prevail in this area.Zone lb represents near—shore lagoonal areas situated far from the "entry—points" of the sands. This zone is characterized by intrabacinal carbonate deposits (oolitic grainstones are relatively frequent). Terrigenous mudstones are also frequent, whereas hybrid arenites and feldspatic litharenites are subordinate.Zone II is the transition zone between the area la and the central part of the lagoon. Terrigenous mudstones and intrabacinal carbonate packstones, wackestones and mudstones prevail. Feldspatic litharenites are locally frequent.Zone III represents the central part of the lagoon and is almost exclusively characterized by wackestones, carbonate mudstones and marls,
Keywords: Facies analysis; Siliciclastic and carbonate lagoonal deposits; Triassic; Northern Italy.